CONTENT VISUAL UNTUK SOSIAL MEDIA BERSAMA PUSAT PENGEMBANGAN ANAK (PPA) GKI SOROGENEN SURAKARTA - Damarjati, FX; Faskaharianto, Kristian; Adinugroho, Suryo; Djong, Alexander Mario Retto (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The large amount of internet use and developments in digital technology today, brought significant influence on all aspects of life. Based on data from We Are Social, 60.4% of the total population in Indonesia or 167 million people are active social media users, and are dominated by young people, both the millennial generation and Z generation. according to that, of course, its require a large amount of a massive stronger visual content today. Visual content on social media is the main thing nowadays. Good social media utilizes the power of visuals to convey a message in an interesting and memorable way. in fact, for today now the campaign of Content is a king has emerged in the public, which means the extraordinary power of content. However, in fact, there are still many young people who do not understand properly how to produce and use good, quality visual content. Therefore, Organization of Pusat Pengembangan Anak (PPA) from Gereja Kristen Indonesia (GKI) Sorogenen Surakarta invites the Bukit Pengharapan Institute of Technology and Christian Business to collaboration and contribute in sharing knowledge through FGDs and counseling regarding Visual Content for Social Media to young people from PPA GKI Sorogenen. The focus of the training material is more on the basic techniques of photography and videography in creating good quality visual content. This community service activity went well without any obstacles, but to have an even greater impact on young people, the suggestion for the future is that activities like this be held with three (3) to four (4) Child Development Center partners from several churches other